1999
DOI: 10.1002/(sici)1097-4571(1999)50:6<505::aid-asi5>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbrowsing: Information customization on the Web

Abstract: The ability to discriminate and distinguish among individual documents in the ever‐increasing volume of information available through digital networks is becoming more and more difficult. With websites being added to the 100 million installed base by tens of thousands per month, information overload is inevitable (H. Berghel, 1997). There are two basic paradigms for dealing with this information overload: filtering (Information filtering, 1992) information before it reaches the end‐user, and customizing the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Sandusky and Tenopir [27] found that, for this type of user, the identification of relevant items in a short time reflects on certain types of behavior as, for instance, the time allocated for reading articles. These results are corroborated by the studies of Berghel et al [4], Shotton [29], Tenopir et al [31,32].…”
Section: • Process Of Indexing and Access Pointssupporting
confidence: 74%
“…Sandusky and Tenopir [27] found that, for this type of user, the identification of relevant items in a short time reflects on certain types of behavior as, for instance, the time allocated for reading articles. These results are corroborated by the studies of Berghel et al [4], Shotton [29], Tenopir et al [31,32].…”
Section: • Process Of Indexing and Access Pointssupporting
confidence: 74%
“…A third general category is systems for customising retrieved information after it arrives. This may operate as a stand-alone facility, or may pick up where filtering systems leave off; see, for example, Berghel et al 42 . Current examples of the customising approach are the refine/categorise features offered by Internet search engines such as AltaVista and Northern Light, which group retrieved sites into subject groupings by statistical analysis of terms; these should reduce the effort of examining large numbers of seemingly relevant web pages.…”
Section: Solutions To Information Overloadmentioning
confidence: 99%
“…"The Xanadu architecture is instantiated in part in the Hyper-G and HyperWave systems. A key idea in this body of work is transclusion, the including of virtual copies of passages from diverse sources into a single document" [53].…”
Section: Citation Context Analysis Of Citing Articles On Information mentioning
confidence: 99%